Hunters, herders and hearths: interpreting new results from hearth row sites in Pasvik, Arctic Norway - Hedman, Sven-Donald; Olsen, Bjørnar Julius; Vretemark, Maria (Rangifer, 2015)
Published version. Source at http://dx.doi.org/10.7557/2.35.1.3334 . The transition from hunting to reindeer herding has been a central topic in a number of archaeological works. Recently conducted archaeological investigation of two interior hearth row sites in Pasvik, Arctic Norway, have yielded new results that add significantly to the discussion. The sites are dated within the period 1000-1300 AD, and are unique within this corpus due to their rich bone assemblages. Among the species represented, reindeer is predominant (87 %), with fish (especially whitefish and pike) as the second most frequent category. Even sheep bones are present, and represent the earliest indisputable domesticate from any Sámi habitation site. A peculiar feature is the repeated spatial pattern in bone refuse disposal, showing a systematic and almost identical clustering at the two sites. Combining analyses of bone assemblages, artefacts and archaeological features, the paper discusses changes in settlement pattern, reindeer economies, and the organization of domestic space. The analyses provide new perspectives on early domestication as well as on the remarkable changes that took place among the Sámi societies in northern Fennoscandinavia during the Viking Age and early Medieval Period.